Analysis of the effect of poverty, unemployment, and population on economic growth in North Kalimantan 2015-2022 - Irwandi Irwandi; Regina Regina; Ahsani Paramita; Nurul Maghfirah Muhliza; Eva Wilina (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2023)
Economic growth is the process of a change in a country's economic condition continuously to a better condition over a certain period. This article will discuss the effect of poverty, unemployment and population on economic growth in North Kalimantan 2015-2022 based on published articles/journals. In addition, the purpose of writing this article is so that we can find out whether poverty, unemployment and population in North Kalimantan affect economic growth. The method used is a type of normative research that examines document studies, and uses secondary data. Secondary data is obtained through data on poverty, unemployment, population and economic growth for the period 2015-2022 in North Kalimantan. After multiple analysis of the results and discussion, it can be concluded that in this study there are several findings. Namely, the number of poor people in North Kalimantan in the 2015-2022 period has a negative or insignificant effect on economic growth and the unemployment rate has a significant or significant effect on economic growth and the total population has no or insignificant effect on economic growth in North Kalimantan Province in 2015-2022. Keywords: Poverty, Unemployment, Population, Economic Growth Economic growth is the process of a change in a country's economic condition continuously to a better condition over a certain period. This article will discuss the effect of poverty, unemployment and population on economic growth in North Kalimantan 2015-2022 based on published articles/journals. In addition, the purpose of writing this article is so that we can find out whether poverty, unemployment and population in North Kalimantan affect economic growth. The method used is a type of normative research that examines document studies, and uses secondary data. Secondary data is obtained through data on poverty, unemployment, population and economic growth for the period 2015-2022 in North Kalimantan. After multiple analysis of the results and discussion, it can be concluded that in this study there are several findings. Namely, the number of poor people in North Kalimantan in the 2015-2022 period has a negative or insignificant effect on economic growth and the unemployment rate has a significant or significant effect on economic growth and the total population has no or insignificant effect on economic growth in North Kalimantan Province in 2015-2022.Keywords: Poverty, Unemployment, Population, Economic Growth